(untitled) (International relations and international law Journal, 2016)
This article describes the concept of contract – deals. Contract as an agreement between two or more persons about the establishment , modification or termination of civil rights and obligations . This definition is explicitly referring to treaty deal. Contracts as their transactions not differing from other legal facts, have no content.They only have arisen from the contract – deals contractual relationship. In this case, as in any other relationship, the content of the contract amount to the mutual rights and obligations of counterparties. In the literature, were made not at all identical views on the concept of agreement as the basis of relationship. For example, the Russian lawyer – scientists M.I. Braginsky and V.V. Vitryansky draws attention to the Uniform Code of U.S. trade.In the Civil Code of the Republic of Kazakhstan with the term «treaty» and «agreement» widely used another concept is to give consent. In comparison with the notion of the concept of consent, agreement does not give rise to the cause of which is peculiar to the legal fact